2012
DOI: 10.1016/j.jcmg.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Coronary CT Angiography and Calcium Score for Major Adverse Cardiac Events in Outpatients

Abstract: The CACS and coronary CTA findings have prognostic value and have incremental value over routine risk factors for MACE, and coronary CTA is superior to CACS. Cardiac CT seems to be a promising noninvasive modality with significant prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
220
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 278 publications
(234 citation statements)
references
References 28 publications
7
220
2
5
Order By: Relevance
“…According to the CONFIRM registry, the absence of CAD is associated with an excellent outcome, whereas the risk for death increases by the extent of CAD. These data were confirmed by a study from Hou et al [21]. In 5007 persons they were able to demonstrate that CTA was superior to CS in terms of predicting cardiovascular events.…”
Section: Prognostic Value Of Ctasupporting
confidence: 52%
“…According to the CONFIRM registry, the absence of CAD is associated with an excellent outcome, whereas the risk for death increases by the extent of CAD. These data were confirmed by a study from Hou et al [21]. In 5007 persons they were able to demonstrate that CTA was superior to CS in terms of predicting cardiovascular events.…”
Section: Prognostic Value Of Ctasupporting
confidence: 52%
“…Studies based on single center and multicenter clinical trials have shown that coronary CT angiography provides incremental prognostic value over clinical risk analysis in predicting major adverse cardiac events with absence of CAD leading to event free survival period, while presence of plaques associated with increased risk of cardiac events [15][16][17][18][19].…”
Section: Disease; Diagnostic Value; Imaging Modalitiesmentioning
confidence: 99%
“…Cardiac PET utilizing 18 F-FDG is considered the most sensitive modality for detecting hibernating viable myocardium and predicting left ventricular functional recovery post-coronary revascularization. PET has higher spatial and temporal resolution than SPECT due to more robust methods of attenuation correction, thus, PET allows quantification of resting and hyperemic regional myocardial perfusion.…”
Section: Journal Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, imaging early calcification is important to identify individuals with enhanced risk of cardiovascular events. Furthermore, many studies have demonstrated coronary artery calcification as a marker for the extent of atherosclerosis and overall plaque burden, and as an important independent predictor of cardiovascular events, mortality, and morbidity 5, 6, 7, 8. Over the past few decades, advanced imaging methods have improved our assessment of atherosclerotic calcification and have provided insights into cardiovascular risk and have contributed to the understanding of the underlying pathophysiologic mechanisms of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%